Business intelligence and data warehousing simplified : 500 questions, answers, and tips - Khan, Arshad (Dulles, VA : Mercury Learning and Information, 2012)
This book targets business and IT professionals who need an introduction to business intelligence and data warehousing fundamentals through a simple question / answer format. Topics include evolution and fundamentals, characteristics and process, architecture and objects, metadata, data conversion, ETL, data storage, infrastructure, data access, data marts, implementation approaches, planning, design, Inmon vs. Kimball, multi-dimensionality, OLAP, facts and dimensions, common mistakes and tips, trends, etc.
Keywords: Business intelligence -- Miscellanea; Business enterprises -- Decision making; Data warehousing -- Miscellanea; Decision making -- Data processing